Strategi Kepala Sekolah Dalam Membangun Budaya Religius Siswa Di SMP Negri 05 Pontianak - Rosiyana; Samiyah (CV Putra Publisher, 2024)
This research aims to examine the principal's strategy in building a religious culture at SMP Negeri 05 Pontianak. The method used is descriptive qualitative with a case study approach. Data collection techniques include observation, interviews and documentation. The research results show that school principals implement various strategies such as implementing routine religious programs, developing a curriculum that is integrated with religious values, creating a supportive school environment, collaborating with parents and the community, and developing teacher professionalism in religious aspects. These strategies involve all school components and aim to create an environment that supports religious values, strengthen the school's commitment to forming students' religious character, and ensure continuity between the values ​​taught at school and those applied in students' homes and social environments. This research concludes that the principal's leadership plays a very important role in achieving these goals